Tinjauan Mendalam Terhadap Hakikat Pendidikan: Menyelusuri Esensi, Tantangan, dan Transformasi - Agustin, Fitri; Kamilia, Afifah Nurani; Nasjwa, Mutiara; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research presents a comprehensive overview of the nature of education, describes the challenges it faces, and explores its transformational potential within the current educational framework. Through a qualitative approach, theme analysis from educational literature, and observations in various learning environments, this research uncovers complex layers in education, highlighting the importance of adaptability, inclusivity, and innovation. The results illustrate challenges around educational equity, technology integration, and changing pedagogical methodologies, while demonstrating the transformational potential of personalized learning, interdisciplinary approaches, and inclusive policies. The research asserts that the essence of education lies in its adaptability to societal changes, inclusive practices, and innovative methodologies, and concludes that education must constantly evolve to meet the needs of diverse learners. By providing deep insights, this research has the potential to contribute to policy makers, educators, and stakeholders, encouraging informed decision making and transformative educational practices for the betterment of society.